Production and characterization of ora-pro-nóbis and agar-agar based edible leathers (Snack-films): a new plant-based food option - de Freitas Pereira, Tiago; de Carvalho, Rosemary Aparecida; Yoshida, Cristiana Maria Pedroso; dos Santos Garcia, Rodrigo Henrique; Veiga-Santos, Pricila [UNESP]; Agneis, Maria Luisa Gonçalves [UNESP]; Seiva, Fábio Rodrigues Ferreira [UNESP]; Martelli, Silvia Maria; Vilela, Danielle Marques; dos Santos Garcia, Vitor Augusto [UNESP] (Elsevier, 2025)
The present study aimed to produce and characterize edible leathers based on ora-pro-nóbis leaf puree (OLP), with concentrations ranging from 30 to 60 g/100 g of ELFM (edible leather forming mass) and agar-agar (3 g/100 g ELFM), using the tape casting technique. The edible leathers were dried in an oven and evaluated for their physicochemical parameters (Aw, moisture, pH, protein content, and hygroscopicity), optical properties (color and browning index), structural characteristics (thickness and SEM), mechanical properties, and spectroscopic profile (NMR). Regardless of the OLP concentration used, it was possible to form leathers from ora-pro-nóbis leaves and agar-agar. Color characteristics were not significantly affected in terms of lightness (L) and chroma a. However, significant differences were observed for chroma b∗ and C∗. The physicochemical stability of the leathers was confirmed by their low water activity (<0.8) and moisture content (<7.8 %). Increasing OLP levels resulted in higher protein content (6.8–8.9 g/100 g w.b.) and thickness (0.3–0.5 mm), which positively impacted puncture resistance and indicated a more cohesive structure. SEM analysis revealed heterogeneous surfaces and internal structures, with discontinuity zones attributed to compounds in the OLP. NMR results confirmed the presence of hemicellulose, lignin, cellulose, and amino acids, reinforcing the nutritional value of the leathers. Additionally, total phenolic content (680–830 mg GAE/g edible leathers) and ABTS•+ (1.272–1.499 μmol Trolox eq./100 g edible leathers) increased with higher OLP content, demonstrating the product’s functional potential. The incorporation of ora-pro-nóbis puree into edible leather formulations contributed to improvements in the nutritional, functional, and structural aspects of the final product. Thus, the developed edible leathers are a promising alternative for using non-conventional vegetables, contributing to innovation in functional and sustainable food products.